Implementation of a GHH roof bolter machine at Merensky shaft (Booysendal Platinum Mine): a case study - Kekana, Wonderboy Orchard (My University, 2018)
Mining Merensky reef successfully at Booysendal Mine will require a machine which enhances team efficiencies delivering results on specified operational and quality parameters. The operational objective of the Booysendal Mine trial of the 3108 ADE Roof bolter was to prove that this machine can mine at 1900 mm stoping width and to set a base for KPIs. The purpose of the upgraded 3108 ADE machine was to achieve to drill and install a bolt in 8 minutes translating in 3 bords supported per shift. This machine had to deliver 235m, 1900 m² per month at stoping width of 1900mm translating to 2.55g/ton in terms of head grade. The objective of this study is to assess the use of industrial engineering techniques to expedite the implementation of a roofbolter in the challenging environment at Booysendal Mine. The process of creating a learning environment is one of the important goals in many business improvement frameworks, and underlies the work done here. To deliver on the above mentioned objectives, this research presents a case study in the use of several industrial engineering techniques:  Lean Manufacturing tools were used to draw up effective communication channels for Operators engagement, visible performance data gathering and performance monitoring.  Observational research methods were used to assess and evaluate the impact of 3108a modifications in achieving the set KPIs per shift in a real underground situation.  The A3 report process was used as the framework to communicate the process of the 3108a machine Roll-out to people on the team. Theory suggests that the method of implementation presented here will create a learning environment, which will in turn meet production targets. The implementation team had set itself a number of production targets, primarily a demand for 42 bolts per shift to be installed and stoping width to be controlled to 1900mm. The targets were based both on benchmarks elsewhere and on economic demands at the mine. iii The study shows that through a step-to-step improvement approach the Operators improved from installing less than 19 bolts per shift to move to 19 – 34 bolts per shift. The 1900mm stoping width target was not consistently achieved. In this study, the author played the role of Project Champion, actioning the knowledge acquired when attending the CMMS courses and applied tools/tactics learned from Trackless Mining and Operations Management courses and tools such as Lean Manufacturing, A3 reports and physical observations. The main thrust of this study was to answer this central question: How well will a set of industrial engineering tools work to improve the modified GHH bolter performance to enable the Merensky shaft to efficiently mine at a stoping width of 1900mm consistently? The research shows that detailed improvement approach delivered more bolts drilled and installed per shift. The report goes further and gives practical on-site implementation team actions taken to ensure a machine delivers 3 bords per shift. Where the implementation team identified challenges outside the scope of this study for addressing the stoping width, the team gave recommendations to relevant technical team on-mine. The tools performed well:  The most successful tool was the use of visual indicators and other elements of communication from Lean to engage Operators and encourage the use of gathering data for process improvement because key feature of Lean is its ability to manage a large number and variety of issues simultaneously using visual prompts to assist in communication of issues.  Lean promotes “going to the Gemba” – managers need to see exactly how things really work. The observational tools used in this implementation showed the value of physical observations because even if 8 minutes per installed bolts was not achieved the implementation team knew exactly where the constraints were and how to tackle it.  The A3 methodology was an effective way of structuring and managing the improvement process in the implementation of the Roof bolter. Through the stepped approach in this case study we managed to deliver exceptional production results six months ahead of planned timeframe.
Keywords: Platinum mines and mining--South Africa; Merensky Reef (South Africa)